IMMIGRATION PROVISIONS AGAINST THE TRAFFIC OF PEOPLE ENTERING / EXITING THE REGION OF INDONESIA - Norbertus Oriwardana; Devina Yuka Utami (Polteknik Imigrasi, 2020)
This paper is based on CHAPTER III Law no. 6 of 2011 concerning Immigration